Thermally Activated Self‐metalation of Carboxy‐functionalized Porphyrin Films on MgO Nanocubes. Issue 17 (19th June 2018) - Kollhoff, Fabian; Schneider, Johannes; Berger, Thomas; Diwald, Oliver; Libuda, Jörg
Abstract: We investigated the adsorption of different free‐base carboxyl‐functionalized porphyrins, 5, 10, 15, 20‐tetrakis(4‐carboxyphenyl)‐21, 23H‐porphyrin (2H‐TCPP) and 5(4‐carboxyphenyl)‐10, 15, 20‐triphenyl‐21, 23H‐porphyrin (2H‐MCTPP), on MgO nanocubes combining IR, UV/Vis and photoluminescence emission spectroscopy. The thermal behavior of the films was monitored in‐situ during annealing. Both porphyrins bind to the nanocubes via one and two acid groups respectively, yielding monolayer films consisting of tilted molecules. For 2H‐TCPP, two acid groups remain free and give rise to a characteristic IR band. Self‐assembly in a tilted adsorbate layer suppresses metalation at room temperature, in contrast to non‐functionalized 2H‐TPP, which adsorbs flat‐lying. Upon heating, 2H‐MCTPP undergoes full metalation at temperatures below 280 °C, whereas 2H‐TCPP does not metalate at all. The hindered metalation reaction is attributed to the rigidity of the adsorbate film preventing complexation. Our results show that the properties of porphyrin films on oxides can be tuned in a wide range via the position and arrangement of carboxyl anchoring groups. Abstract : Adsorption versus metalation : Adsorption on well‐defined MgO nanocubes and subsequent reaction to thermal annealing are studied for the porphyrin derivatives 2H‐MCTPP and 2H‐TCPP. Both materials adsorb on the surface via carboxylates, but because of the different adsorption geometries only 2H‐MCTPP retains enough mobility to be metalated from the MgO at elevated temperatures.